Pembentukan Akar pada Stek Batang Nilam (Pogostemon cablin Benth.) setelah direndam Iba (Indol Butyric Acid) pada Konsentrasi Berbeda - Hasanah, Farida Nur; Setiari, Nintya (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2007)
This paper studies the effect of plant growth regulators, i.e., indol butyric acid (IBA), to the root growth in stem cutting technique of P. cablin, and the correct concentration of the IBA to obtain optimum root growth. The research were carried out in Lab Bio Struktur dan Fungsi Tumbuhan, UNDIP, Semarang. Complete Randome Design was used as the research method in which 4 different concentrations, i.e., control 0, 25, 50 and 75 ppm, were observed with parameter of the amount of the root, the length of the root, wetted weight, dried weight, and efficiency. The results show immersing the stem into 25 ppm IBA exhibits the highest root growth efficiency.